If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + 3 = 15 Reorder the terms: 3 + 3z = 15 Solving 3 + 3z = 15 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 3z = 15 + -3 Combine like terms: 3 + -3 = 0 0 + 3z = 15 + -3 3z = 15 + -3 Combine like terms: 15 + -3 = 12 3z = 12 Divide each side by '3'. z = 4 Simplifying z = 4
| 0.30x+0.30(40)=0.15(130) | | 3y-y=5 | | -2(1)-4(1.5)=6 | | 3(x+2)=-18+9x | | 10t+10.3= | | 3(10+6x)=84 | | (xy-x)dx+(xy+y)dy=0 | | (35x-35)(25x-40)=0 | | 11+5v+3v^2=0 | | -6u=48 | | 4y=-4.4 | | -5x=8+y | | 2x=12+2h | | 4n+4.2= | | -3u=60 | | 2x+(x-2)=10 | | -2x-9x+33=-7 | | -17-9x=-10(1+x) | | 4m=122 | | 4(-9+x)=-12 | | 60^3/12x=0 | | X^2+54+728=0 | | 6x+8y=98 | | 3(1)+6y=12 | | 3z+6=4 | | 8/11(n-19)=64 | | -4v=-9/5 | | -2(-4x+2)=-12 | | 5x+5.7= | | x+.06x=10.6 | | 90+x=220 | | (3k-2)(2k+1)=k(6k+5)-3 |